Reformasi Pelayanan Publik Bidang Izin Mendirikan Bangunan di Daerah - Muhammad Idris (Department of Government Studies Universitas Muhammadiyah Makassar, 2011)
In reformation era, as now, the implementation of the development of specific public services in the service of Building Permit (IMB), it is time to use the principles of quality management-oriented activities to improve and enhance public service delivery is increasingly competitive, and in anticipation of increased globalization and the need received international recognition for quality and process of public service. Public service management system is required with respect to the development of globalization so that the demand for minimum service standards can be actualized in order to improve public services. Thus, the behavior of the bureaucracy in the service delivery of licensing services, local authorities have time to do a public service reformminimum quality standards in public service. Reforms intended primarily; institutional model to a one-stop service, publish a minimum service standards, increase surveillance, patterns of human resource development personnel, and public participation.Di era reformasi seperti sekarang ini, pelaksanaan pengembangan layanan publik tertentu dalam pelayanan Ijin Mendirikan Bangunan (IMB), sekarang saatnya untuk menggunakan prinsip-prinsip manajemen mutu yang berorientasi kegiatan untuk memperbaiki dan meningkatkan pelayanan publik yang semakin kompetitif, dan untuk mengantisipasi perkembangan globalisasi dan kebutuhan mendapatkan pengakuan internasional untuk kualitas dan proses pelayanan publik. Layanan sistem manajemen publik diperlukan sehubungan dengan perkembangan globalisasi sehingga permintaan untuk standar pelayanan minimum dapat diaktualisasikan dalam rangka meningkatkan pelayanan publik. Dengan demikian, perilaku birokrasi dalam pelayanan jasa perizinan, pemerintah daerah memiliki waktu untuk melakukan standar pelayanan publik minimal reformasi kualitas dalam pelayanan publik. Reformasi dimaksudkan terutama; model kelembagaan ke layanan satu atap, menerbitkan standar pelayanan minimum, peningkatan pengawasan, pola personil pengembangan sumber daya manusia, dan partisipasi masyarakat.